2017
DOI: 10.2147/rru.s126134
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic furosemide infusion decreasing early major postoperative renal dysfunction in on-pump adult cardiac surgery: a randomized clinical trial

Abstract: IntroductionAcute renal dysfunction is a common complication of cardiac surgery. Furosemide is used in prevention, or treatment, of acute renal dysfunction. This study was conducted to evaluate the protective effects of intra- and early postoperative furosemide infusion on preventing acute renal dysfunction in elective adult cardiac surgery.MethodsEighty-one patients, candidates of elective cardiac surgery, were enrolled in this study in either the furosemide (n=41) or placebo (n=40) group. Furosemide (2 mg/h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
(34 reference statements)
1
21
1
Order By: Relevance
“…In the study conducted by Fakhari et al, it was found that the rate of AKI after cardiac surgery can be reduced by using furosemide during surgery and in early postoperative period (22). In our study, 36.21% of patients received diuretic therapy during the early postoperative period in the ICU, but it did not influence the rate of AKI.…”
Section: Discussioncontrasting
confidence: 43%
“…In the study conducted by Fakhari et al, it was found that the rate of AKI after cardiac surgery can be reduced by using furosemide during surgery and in early postoperative period (22). In our study, 36.21% of patients received diuretic therapy during the early postoperative period in the ICU, but it did not influence the rate of AKI.…”
Section: Discussioncontrasting
confidence: 43%
“…Our findings of no beneficiary effect of furosemide on post‐operative development of AKI are perhaps not surprising given the effect is predominantly increased urine output but not clearance …”
Section: Discussionmentioning
confidence: 67%
“…We identified 2567 records, whereof 20 full‐text articles were assessed for eligibility (Figure ). A total of four trials comprising a total of 325 patients were included . (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations